RESEARCH OF THE INTERACTION PROCESS OF VACUUM CAPTURE WITH SURFACES OF VARIOUS ROUGHNESS - KARMALITA, ANATOLII; BARTKOV, MYKOLA; PUNDYK, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the process of interaction of a vacuum gripper with surfaces of different roughness, namely, determining the lifting force of a vacuum gripper of a part with a rough surface, with a gap between the plane of the vacuum gripper and the rough surface of the part, taking into account the unevenness of the surfaces and the suction of air from the cavities of the suction cups through a small orifice of the throttle. The tasks of position control and orientation include elements of the problem of object recognition, namely, recognizing the position of objects in relation to the working bodies of technological machines or grippers of industrial robots. Parts with asymmetry of surface properties are divided into those that have asymmetry of hardness, roughness, elasticity, density, electrical conductivity, color, friction coefficient and other properties. A physical model of the process of interaction of the suction cup and the surface of the part has been developed. Factors that affect the implementation of the studied process and the degree of their influence have been determined, namely: parameters of conditional gaps, the value of the supplied vacuum; size of the active part of the suction cup; cross-section size of the calibrated orifice of the throttle; inner radius of the suction cup. The above considerations are valid for the interaction of the working surface of the controlled suction cups and the surface of the part that has irregularities with an open contour. The vast majority of processed materials have such surfaces. Surfaces that have irregularities with a closed contour, created artificially, are less common. A mathematical model has been built to determine the suction force of the suction cup to the surface of the part depending on the parameters of the conditional gaps, the value of the supplied vacuum, the diameter of the orifice of the throttle and the dimensions of the vacuum gripper.